INTERIM MEASURES UNDER PARAGRAPH 10 OF ART. 101 OF THE TAX CODE OF THE RUSSIAN FEDERATION: APPLICATION PRACTICE - N. Z. Zotikov (Вестник университета)
The purpose of tax audits is to verify that the taxpayer complies with the norms of tax legislation. As a rule, in conditions of instability, constantly changing tax legislation, taxpayers violate the norms of the Tax Code of the Russian Federation. In this regard, as a rule, each tax audit ends with additional charges to the taxpayer of taxes, penalties and penalties, which negatively affect their financial position. At the same time, according to the Federal Tax Service of Russia, with a sharp reduction in the number of ongoing on-site tax audits, the amount of additional charges for one on-site audit increases сonstantly: in 2016 – 13.6 million rubles, in 2017 – 15.7 million rubles, 2018 – 22.2 million rubles, 2019 – 33.5 million rubles. The tax authority, by charging additional taxes and penalties to the taxpayer, is interested in collecting them. The current Tax Code of the Russian Federation makes it possible to enforce the decision by taking measures in accordance with paragraph 10 of Art. 101 of the Tax Code of the Russian Federation, the application of which in practice raises many issues. The article considers the practice of applying interim measures.